Formation conditions of granitoids of Middle-Dnieper granite-greenstone area - O. Usenko (Геофизический журнал, 2014)
The paper focuses on revealing conditions of granite formation in the Archean. It has been shown that appearance of the deepest ultrabasic melts, producing comatiites of the konka series is temporarily close to formation of dnipropetrovsk and sura granitoids - 3,11-2,95 Ga ago. A scheme of two-level crystallizing differentiation has been proposed. During granitoids formation considerable role was played by metasomatizing fluids. Up to 2,8 Ga mantle melts were enriched by chlorine-containing water fluid. After 2,8 Ga oxidation potential of deep fluid decreases, while potassium activity increases. Chemical and mineral composition of granites changes.